2018
DOI: 10.14260/jemds/2018/897
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of 3rd Semester MBBS Students Regarding the Medico-Legal Issues in Our Society and the Need for Training in Forensic Medicine- A Descriptive Cross-Sectional Study

Abstract: BACKGROUND The instructional programmes in medical education field are aimed at developing a competent medical officer. However, the current student community gives importance only to cognitive domain, which is essential to get through postgraduate entrance tests. A medical graduate should have sufficient knowledge about medico-legal cases and his role as a responsible learned citizen in assisting the administration of law and justice in the country. Aim: This project is an effort to get an overall picture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…25 The last study tested medical malpracticerelated scenarios in 63 3 rd semester MBBS students at Believers' Church Medical College Hospital and found that only 54% could correctly identify the tested medico-legal concepts. 26 Prior surveys found that medical students are both very concerned about medical malpractice lawsuits in their careers, and that they are not knowledgeable. 5 Our study provides more information regarding specific medical student gaps in medico-legal knowledge and underscores the students' concerns.…”
Section: Resultsmentioning
confidence: 99%
“…25 The last study tested medical malpracticerelated scenarios in 63 3 rd semester MBBS students at Believers' Church Medical College Hospital and found that only 54% could correctly identify the tested medico-legal concepts. 26 Prior surveys found that medical students are both very concerned about medical malpractice lawsuits in their careers, and that they are not knowledgeable. 5 Our study provides more information regarding specific medical student gaps in medico-legal knowledge and underscores the students' concerns.…”
Section: Resultsmentioning
confidence: 99%